Prevalence of metabolic syndrome in elderly Japanese-Brazilians - Xavier, Natasha Priscilla (2012)
Background: Prevalence of individuals with a high cardiovascular risk is elevated in elderly populations. Although metabolic syndrome (MS) increases cardiovascular risk, information is scarce on the prevalence of MS in the elderly. In this study we assessed MS prevalence in a population of elderly Japanese-Brazilians using different MS definitions according to waist circumference cutoff values.Material/Methods: We studied 339 elderly subjects, 44.8% males, aged between 60 to 88 years (70.1 +/- 6.8). MS was defined according to criteria proposed by the Joint Interim Statement in 2009. As waist circumference cutoff point values remain controversial for Asian and Japanese populations, we employed 3 different cutoffs that are commonly used in Japanese epidemiological studies: 1) >90 cm for men and >80 cm for women; 2) >85 cm for men and >90 cm for women; 3) >85 cm for men and >80 cm for women.Results: MS prevalence ranged from 59.9% to 65.8% according to the different definitions. We observed 90% concordance and no statistical difference (p>0.05) in MS prevalence between the 3 definitions. MS diagnosis according to all 3 cutoff values was found in 55.8% of our population, while in only 34.2% was MS discarded by all cutoffs. The prevalence of altered MS components was as follows: arterial blood pressure 82%, fasting glycemia 65.8%, triglyceride 43.4%, and HDL-C levels 36.9%.Conclusions: Elderly Japanese-Brazilians present high metabolic syndrome prevalence independent of waist circumference cutoff values. Concordance between the 3 definitions is high, suggesting that all 3 cutoff values yield similar metabolic syndrome prevalence values in this population.